Study on protocol improvement for spinal muscular atrophy preimplantation genetic diagnosis by using the minisequencing technique - Thi Thanh Nga, Nguyen; Van Khoa, Tran; Thi Hong Van, Nguyen; Truong Giang, Ngo (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
Spinal muscular atrophy (SMA) is a severe neurodegenerative autosomal recessive disorder. Most of patients are caused by the homozygous absence of exon 7 of the telomeric copy of the SMN gene (SMNt) on chromosome. Children with SMA often died prematurely at school age. Therefore, the aim of the study was to improve protocol for spinal muscular atrophy preimplantation genetic diagnosis by using the minisequencing technique. The study was conducted on 30 embryonic cell templates byopsied plus embryos, and four couples were treated using this method. Five unaffected embryos were transferred which resulted in two clinical pregnancy. We have successfully applied the technique of minisequencing for the Preimplantation Genetic Diagnosis of spinal muscular atrophy.